Decentralization and the cultural politics of natural resource management in Kerala, India - Tamara Nair (Singapore Journal of Tropical Geography, 2014)
The state of Kerala in India is known for its active civil society and the massive decentralization campaign launched in 1996. However marginalization of tribal communities hampers the state’s decentralized environmental management strategies. The proposed construction of a dam along the Chalakkudy River will displace two colonies of the Kadar tribe in Chalakkudy and Athirapilly towns, destroy habitats of local wildlife and devastate unique riverine vegetation endemic to the region. This brings to light issues of social and environmental justice as well as a wider responsi- bility to protect and preserve unique flora and fauna. The state’s decentralization strategies, as they relate to tribal communities, lack consideration of local power distribution and cultural condition- ing. This raises questions about the state’s role in social justice as well as biodiversity conservation. In 2010 and 2011, the author’s interviews in Chalakkudy and Athirapilly towns reveal that tribal communities perceive that their place in society restricts their contribution regarding natural resource management and use. The paper suggests that unless the culture of planning and decision making in the state are changed, decentralized strategies will be ineffective, resulting in a predomi- nately top-down approach towards natural resource management, and will negate Kerala’s goal of democratic decentralization.